Office 2021 All-in-One For Dummies - Weverka, Peter (For Dummies, 2022)
Say hello to Office productivity with this one-stop reference With Office 2021 All-in-One For Dummies, you can get up and running with Microsoft's legendary software suite. This update covers all the tweaks you can find in the latest version of Word, Excel, PowerPoint, Outlook, and Teams. You'll also learn how to make these apps work harder for you, because we dig deep into the tips and features that casual Office users might not know about. This edition also offers expanded coverage of Teams and other collaborative tools, so you can nail working from home, or just get a few of those meetings out of the way without having to leave your desk. How can you quickly give documents the same format in Word? What was that one useful Excel function, again? And how does setting up a meeting on Teams work? Office 2021 All-in-One For Dummies serves up quick and simple answers to these questions, along with hundreds of other answers you're expected to know when you work in Office. Learn how Microsoft Office works and get the most out of Word, Excel, PowerPoint, Outlook, and Teams Make amazing charts and graphs that you can plug into your documents, spreadsheets, and presentations Get better at working collaboratively with file sharing options and other neat features Do more, faster with expert tips and guidance on the full suite of Office software for 2021 Whether you're new to Office or just need a refresher for the newest updates, the nine mini-books inside are your keys to getting stuff done.
Vendor-supplied metadata
Keywords: Microsoft Office; Microsoft Word; Microsoft Excel (Computer file); Microsoft PowerPoint (Computer file); Microsoft Outlook; Microsoft Access; Word processing; Electronic spreadsheets; Database management -- Computer programs; Word Processing; Database Management Systems; Traitement de texte; Tableurs; Bases de données; Gestion; Logiciels; Database management; Computer programs